Discrete and computational geometry and graphs : 18th Japan Conference, JCDCGG 2015 Kyoto, Japan, September 14-16, 2015, revised selected papers /: 18th Japan Conference, JCDCGG 2015 Kyoto, Japan, September 14-16, 2015, revised selected papers. ([2016]) - Unknown
No abstract available